An oscillating Min system in Bacillus subtilis influences asymmetrical septation during sporulation - Jamroškovič, Ján (Society for General Microbiology, 2012)
The Min system plays an important role in ensuring that cell division occurs at mid-cell in rod-shaped bacteria. In Escherichia coli, pole-to-pole oscillation of the Min proteins specifically inhibits polar septation. This system also prevents polar division in Bacillus subtilis during vegetative growth; however, the Min proteins do not oscillate in this organism. The Min system of B. subtilis plays a distinct role during sporulation, a process of differentiation which begins with an asymmetrical cell division. Here, we show that oscillation of the E. coli Min proteins can be reproduced following their introduction into B. subtilis cells. Further, we present evidence that the oscillatory behaviour of the Min system inhibits sporulation. We propose that an alternative Min system mechanism avoiding oscillation is evolutionarily important because oscillation of the Min system is incompatible with efficient asymmetrical septum formation and sporulation.